Maturity level in Management Services Processes’ based on BPM - Cruz, Joseph (2011)
Companies at global level, use to suffer a higher dependency on information te- chnology, not just for operational maintenance of level of organization levels, but also for increasing the business worth through use of data and specially through analysis and optimizing its processes. The methodology Business Process Mana- gement (BPM) when combining with the good practices proposed by Information Technology Infrastructure Library (ITIL), it gets the opportunity to increase the value of any company through processes improvement and adjustment from a better and agile view, stronger with the ability to adapt to adjustments, allowing the organizations to aim their processes to the customer.